Application of probabilistic approaches to the performance evaluation of building envelopes to withstand mould growth. (November 2019) - Gradeci, Klodian; Berardi, Umberto
Probabilistic-based approaches for the performance evaluation of building envelopes to withstand mould growth have gained significant attention in recent years. In this article, a scoping review is performed to identify some current challenges and opportunities in probabilistic-based approaches. Therefore, the performance of a highly insulated wall is evaluated by applying a probabilistic-based methodology that accounts for several uncertainties and investigates their significance. A sensitivity analysis is performed according to the Morris method to understand the influence of each parameter and simplify the system representation of this case study. Deficiencies in terms of rain penetration and air leakage are accounted for. The mould growth risk is evaluated by integrating different mould models and assessment criteria. Overall, the performance of the investigated wall is found satisfactory in most of the cases, except when wind-driven rain penetration occurs. The study demonstrates that a probabilistic-based methodology enables a systematic approach to evaluate the performance of building constructions as it accounts for the involved uncertainties, provides a clear association of the microbial growth to its probability of occurrence and enables the identification of the dominant parameters, delivering more comprehensive conclusions.